94.3k views
4 votes
What’s the answer for this problem? It’s okay if you can just show me what’s the inverse for this equation

What’s the answer for this problem? It’s okay if you can just show me what’s the inverse-example-1

1 Answer

5 votes
Answer:
Inverse\text{ of function y = }\frac{(x\text{ +}1)^2}{9}-2

Step-by-step explanation:

Given:


\text{y = 3}√(x+2)\text{ - 1}

To find:

the inverse of the function

To determine the inverse of the function, first we will interchange x and y:


x\text{ = 3}\sqrt{y\text{ + 2}}\text{ - 1}

Next is to solve for y by making it the subject of formula


\begin{gathered} x\text{ = 3}\sqrt{y\text{ +2}}\text{ -1} \\ Add\text{ 1 to both sides:} \\ \text{x + 1 = 3}\sqrt{y\text{ + 2}} \\ \\ divide\text{ both sies by 3:} \\ \frac{x\text{ + 1}}{3}=\text{ }\frac{\text{3}\sqrt{y\text{ + 2}}}{3} \\ \frac{x\text{ + 1}}{3}=\text{ }\sqrt{y\text{ + 2}} \end{gathered}
\begin{gathered} square\text{ both sides:} \\ (\frac{x\text{ + 1}}{3})^2\text{ = \lparen}√(y+2))^2 \\ (\frac{x\text{ + 1}}{3})^2\text{ = y + 2} \\ \\ subtract\text{ 2 from both sides:} \\ (\frac{x\text{ + 1}}{3})^2\text{ - 2 = y } \\ y\text{ = \lparen}\frac{x\text{ + 1}}{3})^2\text{ - 2 = }\frac{(x\text{ + 1\rparen}^2}{3^2}\text{ - 2} \\ \\ y\text{ = }\frac{(x\text{ + 1\rparen}^2}{9}-2 \end{gathered}
Inverse\text{ of function y = }\frac{(x\text{ +}1)^2}{9}-2

User Asosnovsky
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.